In vivo patch-clamp analysis of response properties of rat primary somatosensory cortical neurons responding to noxious stimulation of the facial skin - Nasu Masanori; Takahashi Masayuki; Takeda Mamoru; Matsumoto Shigeji (SAGE Publishing, 2010)
Abstract Background Although it has been widely accepted that the primary somatosensory (SI) cortex plays an important role in pain perception, it still remains unclear how the nociceptive mechanisms of synaptic transmission occur at the single neuron level. The aim of the present study was to examine whether noxious stimulation applied to the orofacial area evokes the synaptic response of SI neurons in urethane-anesthetized rats using an in vivo patch-clamp technique. Results In vivo whole-cell current-clamp recordings were performed in rat SI neurons (layers III-IV). Twenty-seven out of 63 neurons were identified in the mechanical receptive field of the orofacial area (36 neurons showed no receptive field) and they were classified as non-nociceptive (low-threshold mechanoreceptive; 6/27, 22%) and nociceptive neurons. Nociceptive neurons were further divided into wide-dynamic range neurons (3/27, 11%) and nociceptive-specific neurons (18/27, 67%). In the majority of these neurons, a proportion of the excitatory postsynaptic potentials (EPSPs) reached the threshold, and then generated random discharges of action potentials. Noxious mechanical stimuli applied to the receptive field elicited a discharge of action potentials on the barrage of EPSPs. In the case of noxious chemical stimulation applied as mustard oil to the orofacial area, the membrane potential shifted depolarization and the rate of spontaneous discharges gradually increased as did the noxious pinch-evoked discharge rates, which were usually associated with potentiated EPSP amplitudes. Conclusions The present study provides evidence that SI neurons in deep layers III-V respond to the temporal summation of EPSPs due to noxious mechanical and chemical stimulation applied to the orofacial area and that these neurons may contribute to the processing of nociceptive information, including hyperalgesia.